ISSUES OF DATA SUPPORT FOR FRAUD DETECTION IN THE BANKING SECTOR - Dmitry A. Suslov; Dmitry M. Sedov (Статистика и экономика, 2016)
This article discusses problems of information provision of operative-investigative activities, aimed at curbing fraudulent activities in the banking sector. The central place in the article is devoted to issues of application of legislation in the part of bank secrecy, the ratio of its interests, as banks and commercial organizations, the state, through its economic institutions and law enforcement agencies.